Financial Development and the Social Cost of Financial Intermediation in Africa. Issue 4 (2nd October 2018) - Gyeke-Dako, Agyapomaa; Agbloyor, Elikplimi Komla; Turkson, Festus Ebo; Baffour, Priscilla Twumasi
ABSTRACT: This article investigates the effect of financial development on the social costs of financial intermediation across a large number of banks in Africa. The study distinguishes between countries that are financially developed and those that are not financially developed to examine the impact of financial development on the social costs of financial intermediation. A sample of 260 banks from 29 countries in Africa is used over an 8-year period from 2006 to 2013. We employ both Random Effect and GMM techniques to resolve the issues of unobserved heterogeneity and endogeneity. We observe that overall, financial development reduces the social costs of intermediation. We also determine that the social costs of intermediation are lower for countries that have more developed financial systems compared to those with less developed financial systems. Our study is useful because it suggests that if countries want to reduce their social costs of intermediation, they should develop their financial systems.